Screening, Identification and Enzymatic Properties Study of Cold-adapted Marine Pectinase-Producing Bacteria - Ziqi ZHAO; Yeyu LIU; Shuang YU; Xuemei CHI; Shuhan JIN; Ligong CHEN; Qingfang ZHANG; Xiaohui WANG (Shipin gongye ke-ji, 2024)
Objective: To select novel strains that could degrade pectin at low temperature from marine sediment samples and discover pectinase with potential industrial value. Methods: Take pectin as the only carbon source, screening a high-yielding pectinase strain from sea mud in Bohai Bay, Dalian with the transparent circle method and the 3,5-dinitrosalicylic acid method (DNS method). It analyzed the morphological, physiological and biochemical characteristics, and determined the 16S rDNA sequence. After comparing BLAST homologous gene, it built up a phylogenetic tree, and further studied the enzymatic properties. Results: It screened the strain with high pectinase yield which was named LY-1. Then it analyzed the 16S rDNA sequence and determined that this strain was Streptomyces olivogriseus from the physiological and biochemical index. When strain LY-1 was cultured at 25 ℃ and 180 r/min for 24 hours, the enzyme activity of pectinase was 30.56 U/mL. It showed that the optimal enzyme pH was 8.0, and the optimal enzyme temperature was 20 ℃. Furthermore, the enzymatic activity could still be maintained more than 70% when it was incubated at 60 ℃ for 2 hours, and remained stable in the pH range of 7.0~9.0 with enzyme activity at over 90%. The metal ions Cu2+, Ba2+, Mg2+, Ca2+, K+, and Co2+ could promote the activity of this enzyme, while Mn2+, Zn2+, Hg2+, and Na+ would inhibit its activity. Conclusion: The pectinase produced by strain LY-1 would have the potential to be applied to industrial commercial pectinase.